Open Education in Practice – How Policy Can Lead to Positive Change. Issue 3 (3rd July 2017) - Stevens, Jessica; Bradbury, Stephanie; Hutley, Sue
Abstract: The use and creation of Open Education Resources (OER) is becoming increasingly prevalent with teachers and learning designers at universities around the world. OER allows educators to create content and make their content available to the world under an open licence, and also provides the opportunity to use and adapt other OER content. Whilst the use and creation of OER in tertiary institutions is not yet considered the 'norm', many jurisdictions around the world have taken steps, to fund, support and encourage the use of OER in their educational institutions. The Queensland University of Technology (QUT) has developed an Open Education (OE) initiative to support the use and creation of OER at QUT. Policy is often the foundation stone, which supports progress and change. The underlying policy provides the framework and often points to the legal parameters that guide the objectives of the project or movement. The importance of policy is evident in the way in which QUT has developed and implemented an OE initiative to promote and support the creation and use of OER. This paper considers the history and development of OER, using QUT's OE initiative as an example of the ways in which policy and implementation can lead to positive change.